Targeting of tumor cells by custom antigen transfer: a novel approach for immunotherapy of cancer - Nesi, Ilaria; Della Bella, Chiara; Taddei, Maria Letizia; Santi, Alice; Pranzini, Erica; Paoli, Paolo; D’Elios, Mario Milco; Ramazzotti, Matteo; Genovese, Massimo; Caselli, Anna; Cirri, Paolo (Frontiers in Oncology, 2023)
In the early stages of carcinogenesis, the transformed cells become "invisible" to the immune system. From this moment on, the evolution of the tumor depends essentially on the genotype of the primitive cancer cells and their subsequent genetic drift. The role of the immune system in blocking tumor progression from the earliest stages is largely underestimated because by the time tumors are clinically detectable, the immune system has already completely failed its task. Therefore, a clinical treatment capable of restoring the natural anti-tumor role of the immune system could prove to be the "ultimate weapon" against cancer.Herein, we propose a novel therapeutic approach for the treatment of solid cancer that exploits the capability of activated monocytes to transfer major histocompatibility complex I (MHC-I) molecules bound to antigenic peptides to cancer cells using microvesicles as cargo, making tumor cells target of a "natural" CD8 + T lymphocyte cytotoxic response.